2021
DOI: 10.1016/j.chaos.2020.110601
|View full text |Cite
|
Sign up to set email alerts
|

Stationary distribution and probability density function of a stochastic SVIS epidemic model with standard incidence and vaccination strategies

Abstract: Highlights A stochastic SVIS epidemic model with standard incidence and vaccination is established. The existence and uniqueness of an ergodic stationary distribution is obtained under If, we derive the exact expression of density function of the stochastic model around the quasi-stable equilibrium. Some criteria for the disease extinction are obtained. Parameter analyses are studied to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Combining the Routh‐Hurwitz stability criterion 46 and Zhou et al, 47 a solving theory of a special algebraic equation is shown in the following Lemma .…”
Section: Models Notations and Necessary Lemmasmentioning
confidence: 98%
“…Combining the Routh‐Hurwitz stability criterion 46 and Zhou et al, 47 a solving theory of a special algebraic equation is shown in the following Lemma .…”
Section: Models Notations and Necessary Lemmasmentioning
confidence: 98%
“…This population is divided into susceptible vaccinated infected populations at any instant In this study, the susceptible individuals obey the rule of logistic growth model which is the growth process of species in natural way (Jiang et al 2007 ; Arino et al 2006 ; Xu et al 2015 ). We formulate a deterministic SVIS epidemic system (Zhou et al 2020 , 2021 ) with saturated incidence and vaccination strategies, which is given as where and are all positive constants. The parameter is the intrinsic growth rate of susceptible individuals, and depicts the carrying capacity of The term is more sensitive than the bilinear incidence rate in epidemiological study (Zhu et al 2020 ; Xu et al 2016 ; Batabyal and Batabyal 2021 ; Chong et al 2014 ).…”
Section: Model Calibration and Dynamical Behaviormentioning
confidence: 99%
“…The existence of ergodic stationary distribution and the probability density function of the SVIS epidemic model were studied by Zhou et al ( 2020 ). Zhou et al ( 2021 ) solved the general three-dimensional Fokker–Planck equation. The existence of stationary distribution and ergodicity of the system has been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…is a positive definite matrix on the basis of Zhou et al 28, Lemma 2.3, and c 1 > 0 is the minimum eigenvalue of matrix Θ0 .…”
Section: Dynamical Analysis and Density Function For The Model With B...mentioning
confidence: 99%